2014
DOI: 10.1104/pp.113.231688
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of Water Transport across Epidermal Cell Membranes in Tradescantia virginiana      

Abstract: Using the automated cell pressure probe, small and highly reproducible hydrostatic pressure clamp (PC) and pressure relaxation (PR) tests (typically, applied step change in pressure = 0.02 MPa and overall change in volume = 30 pL, respectively) were applied to individual Tradescantia virginiana epidermal cells to determine both exosmotic and endosmotic hydraulic conductivity (L p OUT and L p IN , respectively). Within-cell reproducibility of measured hydraulic parameters depended on the method used, with the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Furthermore, it has been reported that 0.2 MPa of pressure differences induce plasmodesmatal closure in Nicotiana clevelandii cells [ 27 ]. Significant decreases in membrane hydraulic conductivity have been observed at 1 min after 0.1–0.2 MPa of hydraulic disturbance was instantly given [ 28 , 29 ]. Hence, if turgor pressure was altered in a cell, the hydraulic pressure differential would be rapidly transmitted to the nucleus and other organelle compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that 0.2 MPa of pressure differences induce plasmodesmatal closure in Nicotiana clevelandii cells [ 27 ]. Significant decreases in membrane hydraulic conductivity have been observed at 1 min after 0.1–0.2 MPa of hydraulic disturbance was instantly given [ 28 , 29 ]. Hence, if turgor pressure was altered in a cell, the hydraulic pressure differential would be rapidly transmitted to the nucleus and other organelle compartments.…”
Section: Introductionmentioning
confidence: 99%
“…The cell pressure probe is an excellent tool to acquire data on parameters such as cell turgor, cell wall elasticity, and membrane permeability and has been optimized for a number of cell types over the last decades (Steudle and Zimmermann, 1977;Hüsken et al, 1978;Cosgrove 1981Cosgrove , 1985Cosgrove , 1993Shackel and Brinckmann, 1985;Cosgrove et al, 1987;Oparka et al, 1991;Ye and Steudle, 2006;Wada et al, 2014). Unfortunately, some cell types show rapid injury responses, which make it difficult or impossible to apply this method.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, wall elastic modulus ( ε ) and cell hydraulic conductivity ( L p ) were measured with a CPP in control cells ( T = 0 h). By applying < 0.1 MPa of pressure pulses, ε was determined by ε = V·ΔP/ΔV after the Ψ p measurement according to the previous studies 29 , 64 . The L p is given by L p = ln(2) V /( AT 1/2 ( ε + π )) 29 , where A is the cell surface area, and π is the cell osmotic pressure (i.e., − Ψ s ) determined with the nanoliter osmometer.…”
Section: Methodsmentioning
confidence: 99%